The influence of debt to asset ratio, total asset turnover, and net profit margin on return on assets in the Banking Subsector listed on the Indonesia Stock Exchange (2019-2022) - Hasanatun, Umi; Saragi, Melisa Bella; Tailisha, Wenny; Angelyn, Delysia; Helman, Helman; Yunita, Mella (Journal of Economics and Business Letters, 2025)
This study investigates the impact of the debt-to-asset ratio (DAR), Total Asset Turnover (TATO), and Net Profit Margin (NPM) on the financial performance of banking companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2022. Return on Assets (ROA) is used as the dependent variable to measure profitability. Drawing on secondary data from 27 purposively selected banks over four years, this study employs multiple linear regression analysis supported by classical assumption tests to ensure model robustness. The results show that DAR has a significantly negative effect on ROA, indicating that excessive leverage can undermine asset-driven profitability. Conversely, both TATO and NPM exert significant positive effects on ROA, suggesting that efficient asset utilization and strong cost control are key drivers of financial performance in the banking sector. The findings also reveal that DAR, TATO, and NPM jointly explain 97% of the variation in ROA, highlighting the integrated influence of capital structure, operational efficiency, and profit-margin management. This study contributes to the literature by offering a post-pandemic assessment of profitability drivers in the Indonesian banking context and provides practical implications for bank managers, regulators, and investors aiming to optimize performance in an increasingly digitized and regulated environment.